Time-resolved luminescence spectroscopy for monitoring the stability and dissolution behaviour of upconverting nanocrystals with different surface coatings. Issue 23 (5th June 2020) - Andresen, Elina; Würth, Christian; Prinz, Carsten; Michaelis, Matthias; Resch-Genger, Ute
Abstract : We demonstrate the potential of time-resolved luminescence spectroscopy for the straightforward assessment and in situ monitoring of the stability of upconversion nanocrystals (UCNPs). Abstract : We demonstrate the potential of time-resolved luminescence spectroscopy for the straightforward assessment and in situ monitoring of the stability of upconversion nanocrystals (UCNPs). Therefore, we prepared hexagonal NaYF4 :Yb 3+, Er 3+ UCNPs with various coatings with a focus on phosphonate ligands of different valency, using different ligand exchange procedures, and studied their dissolution behaviour in phosphate-buffered saline (PBS) dispersions at 20 °C and 37 °C with various analytical methods. The amount of the released UCNPs constituting fluoride ions was quantified by potentiometry using a fluoride ion-sensitive electrode and particle disintegration was confirmed by transmission electron microscopy studies of the differently aged UCNPs. In parallel, the luminescence features of the UCNPs were measured with special emphasis on the lifetime of the sensitizer emission to demonstrate its suitability as screening parameter for UCNP stability and changes in particle composition. The excellent correlation between the changes in luminescence lifetime and fluoride concentration highlights the potential of our luminescence lifetime method for UCNP stability screening and thereby indirect monitoring of the release of potentially hazardous fluoride ions during uptake and dissolution in biological systems. Additionally, the developed in situ optical method was used to distinguish the dissolution dynamics of differently sized and differently coated UCNPs.